Morphological and molecular analyses demonstrate identification problems of Anopheles nuneztovari (Diptera: Culicidae) using dichotomous keys - GÓMEZ, GIOVAN F.; CIENFUEGOS, ASTRID V.; GUTIÉRREZ, LINA A.; CONN, JAN E.; CORREA, MARGARITA M. (Revista Colombiana de Entomología, 2010)
The Oswaldoi Group, subgenus Nyssorhynchus (Diptera: Culicidae), includes 16 species. Some of these species exhibit high intraspecific morphological variability and interspecific similarity; this can lead to difficulty in the identification of females by using morphological keys, as is the case with Anopheles nuneztovari, considered a primary malaria vector in Colombia. In this study we compared the usefulness of five morphological keys for the identification of A. nuneztovari specimens collected in the locality of Puerto Anchica, Montelibano, Córdoba, Colombia. Three morphometric ratios were analyzed and morphological identification results were confirmed using the PCR-RFLP technique based on ITS2 sequences. The analysis of 41 females using the keys showed that A. nuneztovari specimens presented overlap with other species of the Oswaldoi Group, such as A. rangeli, A. oswaldoi, A. evansae and A. benarrochi. Molecular analysis confirmed that all of the specimens corresponded to A. nuneztovari. Because the use of morphological keys continue to be a strategy of choice for the identification of anophelines, the results suggest that in the case of problematic species, it is convenient to confirm identification using molecular methods developed with the support of the identification of immature stages.